Evaluation of hematologic variables in newborn C57/BL6 mice up to day 35. (30th December 2015) - White, Jessica R.; Gong, Huiyu; Colaizy, Tarah T.; Moreland, Jessica G.; Flaherty, Heather; McElroy, Steven J.
Abstract : Background: Hematologic variables are often analyzed in animal analogs during the investigation of complex disease etiologies such as necrotizing enterocolitis. However, reference intervals (RI) can vary depending on animal strain, age, and sampling site. Reference intervals have been published for adult C57BL/6J mice, but not newborn C57BL/6J mice. Objectives: The purpose of the present study was to determine hematologic RI in newborn C57BL/6J mice up to day 35. Methods: C57BL/6J mice founders from The Jackson Laboratory were bred at the University of Iowa. Blood samples were obtained via facial vein sampling at postnatal days 0 (p0), p7, p14, p21, p28, or young adulthood (p35). CBCs were determined with the Sysmex XT‐2000iV analyzer within 30 minutes of blood collection at a 1:10 dilution. Statistics were determined using nonparametric methods following ASVCP guidelines. Results: Hematologic RI were determined for each of the 6 groups ( n = 247, n ≥ 39 per group). Significantly higher values for HGB, RBC, and PLT counts were observed with advancing developmental age. Total WBC counts remained relatively stable during the first 35 days of life. However, WBC differential counts were dominated by neutrophils and lymphocytes in the younger mice, with a trend toward a lymphocytic leukogram on day 35. Conclusions: These results illustrate the dynamic changes in hematologic variables during murine development after birth. Utilization of age‐specific RI is advised when evaluating data derived from experimental perinatal mouse models.